Penerapan Algoritma Naïve Bayes Untuk Analisis Pengaruh Faktor Pendidikan Terhadap Peningkatan Kesehatan Masyarakat - Fathurrahman, Fathurrahma; Yupi Kuspandi Putra; Muh. Adrian Juniarta Hidayat (Fakultas Teknik Universitas Hamzanwadi, 2024)
Health and Education are the main capital in realizing the nation's progress. Because quality and productive human resources are those who have a good level of health. People who have low education usually cannot receive current information about health, they prefer traditional health care such as going to a shaman or healer rather than going to the doctor. The aim of this research is to determine the influence of educational factors on public health. Data obtained through surveys and data collection carried out in the Sustainable Development Goals (SDGs) program or what we can interpret as sustainable development goals. 4429 data were obtained which included: economic data, health data, poverty data, gender data, education data and environmental data. The data obtained is used by researchers as attributes or variables to support decision making. This research uses a classification method with the Naïve Bayes algorithm with the accuracy value as the final value of the research. Data processing uses Rapid Miner software. From the test results it turns out to have an accuracy rate of 65.19%. Testing was carried out using k-fold validation, starting from k-fold validation 2 to 10. And the highest accuracy value was found at k-fold 6